Factors Affecting The Effectiveness of Inclusive Education - Kodirova, Feruzakhon Usmanovna; Khimmataliyev, Dustnazar Omonovich; Akhlan, Riksma Nurahmi Rinalti; Safiyeva , Mokhinur Akramovna (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
The article describes the results of experimental and test work aimed at effectively organizing inclusive education and determining the factors affecting the successful implementation of the academic and social activities of children with disabilities in the pedagogical process. The experimental work was carried out in 17 schools in 4 cities of the country. 117 healthy , 53 disabled primary students, parents of the students, 45 educators were involved. During the study, methods of statistical analysis of Social Survey, observation, interview, picture keys, results were used. One important factor is the availability of resources and support services. Another factor is the attitude and thinking of teachers, students and parents towards inclusion. A positive attitude, the acceptance and support of all stakeholders will help create an inclusive culture in schools and classrooms. Conversely, a negative attitude, lack of support and understanding can hinder the success of inclusive education initiatives.